Metal‐Doped Nitride‐Based Nanostructures for Saving Sustainable and Clean Energy in Batteries - Mollaamin, Fatemeh; Monajjemi, Majid (Wiley, 2025)
ABSTRACTThe hypothesis of the energy adsorption phenomenon was confirmed by density distributions of CDD, TDOS, and LOL for GaN and ternary alloys of AlGaN and InGaN. Based on TDOS, the excessive growth technique on doping manganese is a potential approach to designing high‐efficiency hybrid semipolar gallium nitride–based devices in a long wavelength zone. A vaster jointed area engaged by an isosurface map for Mn doping GaN, AlGaN, and InGaN toward formation of nanocomposites of Mn@GaN–H, Mn@AlGaN–H, and Mn@InGaN–H after hydrogen adsorption due to labeling atoms of N(4), Mn(5), and H (18), respectively. Therefore, it can be considered that manganese in the functionalized Mn@GaN, Mn@AlGaN, or Mn@InGaN might have more impressive sensitivity for admitting the electrons in the status of hydrogen adsorption. Furthermore, Mn@GaN, Mn@AlGaN, or Mn@InGaN are potentially advantageous for certain high‐frequency applications requiring batteries for energy storage. The advantages of manganese over GaN, AlGaN, or InGaN include its higher electron and hole mobility, allowing manganese doping devices to operate at higher frequencies than nondoping devices. A comprehensive investigation on hydrogen grabbing by heteroclusters of Mn‐doped GaN, AlGaN, and InGaN was carried out using DFT computations. The position of the Mn‐doped energy states was evaluated via the spectra obtained from the bipolar devices with the Mn‐doped GaN/AlGaN/InGaN as an active layer.